La gouvernance des migrations subsahariennes au prisme de la politique de dispersion spatiale au Maroc - Sofia El Arabi (L'Espace Politique)
This article provides an analysis of sub-Saharan migration governance in the light of the policy of spatial dispersal as a new modality of bordering in Morocco, in the post-2015 Valletta Migration Summit context. By conducting participatory action research over the period 2017-2020 with a cohort of 215 migrants dispersed by Moroccan authorities and focusing on two Moroccan cities (Tiznit and Taza), we explore the border and territorial turn in Morocco in migration management. The evolution of the forms and uses of the Euro-Moroccan border and the biopolitics of spatial dispersal operate according to the logic of division of spatial labour serving a territorial confinement of migrants. We show that the adaptation of national borders to the new mobility regime, by thickening for certain categories of individuals and weakening for others, is part of a new framework of local migratory governance developed on the basis of territorialization. The analysis of the protection-development nexus informs us of the rhetoric of the fixation of dispersed migrants in Morocco and about forced mobility as a new instrument of a soft geopower.